PRIORITY SETTING IN GLOBAL HEALTH: TOWARDS A MINIMUM DALY VALUE. (9th April 2013) - Drake, Tom
SUMMARY Rational and analytic healthcare decision making employed by many national healthcare‐funding bodies could also be expected from global health donors. Cost effectiveness analysis of healthcare investment options presents the effectiveness of a particular action in proportion to the resources required, and cost effectiveness thresholds, while somewhat arbitrary, define the level at which the investment can be considered value for money. Currently, cost effectiveness thresholds reflect the national budget context or willingness‐to‐pay, which is problematic when making cross‐country comparisons. Defining a global minimum monetary value for the disability adjusted life year (DALY) would in effect set a global baseline cost effectiveness threshold. A global minimum DALY value would reflect a universal minimum value on human health, irrespective of a national provider's willingness or ability to pay. A minimum DALY value and associated threshold has both limitations and flaws but is justified on similar grounds to the Millennium Development Goals or the absolute poverty threshold and has the potential to radically improve transparency and efficiency of priority setting in global health. Copyright © 2013 John Wiley & Sons, Ltd.